INVESTIGATION OF HEALTH EFFECT OF FRUIT JUICE FROM LINGONBERRY (VACCINIUM VITIS - IDEA) VIA PHYSICOCHEMICAL METHODS - Poli Radusheva; Iliana Milkova-Tomova; Krastena Nikolova; Dragomira Buhalova; Iordanka Aleksieva; Tinko Eftimov; Stefan Krustev (Peytchinski Publishing, 2017)
Objective: Antioxidants reduce cell damaging effects of free radicals, they also are used as medications to treat various forms of brain injury. Forest fruits as a lingonberry contain a lot of flavonoids and antioxidant supplements which contribute to the protection of different types of cancers and cardiovascular health problems. Purpose: The aim of this study is to explore the relations between natural fluorescence in juice from lingonberry and its total phenolic content and total antioxidant capacity in view of the usefulness of these compounds for human health and hygiene of food. Materials and Methods: For this reason, the juices from lingonberry from the region of Velingrad еnriched with lactulose will be investigated by using optical methods (colour measuring, fluorescence spectroscopy), rheological properties and sensor analysis. It may be an alternative method for quantifying the phenols and vitamins in juice from wild berries. Results: The dependences between chemical parameters, colour characteristics and the ratio between the intensity of emission and the intensity of excitation for exciting wavelength 275 nm have been found. The dependence between antioxidant activity and total phenolic content also exists. Excitation in the UV region is suitable for distinguishing the phenolic content and antioxidant compounds. The most suitable wavelengths found to be 265 nm and 275 nm. Lingonberry juices with lactulose exhibited non-Newtonian behaviour and Ostwald-de-Waele model are applied to calculate its rheological properties. Conclusions: The natural fluorescence of the lingonberry juices was correlated with their antioxidant properties, total phenolic content and lightness. From fluorescence spectra three groups of fluorescence components are determined - phenolic acids, tannins and flavonoids. The obtained results and discussion presented here give the direction for further studies and additional test for validation of the correlation between fluorescence intensity and phenolic compounds. In the future investigation, the fluorescence in the visible region will be used for determining the content of vitamins. The fluorescence spectroscopy is a promising technique for the rapid screening of lingonberry juice for antioxidant and phenolic content. The rheological behaviour of pasteurised juice from lingonberry showed a pseudoplastic behaviour.